Epileptic seizure first aid practices of publics in Northwest Ethiopia 2021: Unsafe practices of nearly three-fourths of the community - Asnakew, Sintayehu; Legas, Getasew; Belete, Amsalu; Beyene, Getnet Mihretie; Tedla, Assasahegn; Shiferaw, Kirubel; Mengist, Birhanu; Bayih, Wubet Alebachew; Feleke, Dejen Getaneh; Birhane, Binyam Minuye; Chanie, Ermias Sisay; Birhan, Zelalem; et al. (Frontiers in Neurology, 2022)
Background Religious and socio-cultural beliefs influence how people with epilepsy are treated and cared for. Many communities in Africa and other developing countries, including Ethiopia, believe that epilepsy is caused by evil spirits and that treatment using herbal plants should be performed by traditional doctors and religious leaders. The combination of these socio-cultural beliefs and the communities’ level of awareness towards epilepsy affect the first aid practices in managing epileptic seizures. Objectives: This study aimed to assess the public first aid practice of epileptic seizure and its associated factors in North West Ethiopia, South Gondar zone, Amhara, Ethiopia 2021. Methods: A multi-center community-based cross-sectional study was conducted by using a previously adapted standard questionnaire. A multistage cluster sampling technique was applied. A total of 756 participants were approached and 741 respondents completed the questionnaire with a response rate of 98.02%. Data were entered into Epi data version 4.4.2 and then exported to SPSS version 24 for analysis. Descriptive and analytical statistical procedures, bivariate and multivariate binary logistic regressions with odds ratios and 95% confidence interval were employed. The level of significance of association was determined at a p-value < 0.05. Results: Overall, 71.7% (95CI; 68.3, 74.9) of the South Gondar community had unsafe practice measures in managing patients with seizure episodes. Individuals who couldn’t read and write (AOR=1.99, CI95%; 1.00.3.97), participants who did not take training related to epilepsy (AOR=2.07, CI95; 1.35, 3.17) participants who had poor knowledge about (AOR=1.51, CI95%; 1.06, 2.14) and negative attitude towards epilepsy (AOR=2.20, CI95%; 1.50, 3.22) had unsafe practice compared with their counterparts. Conversely, participants who reached secondary education had safe practice measures (AOR=0.4, CI95; 0.26, 0.63) in managing epileptic seizures. Conclusions: In this study, large numbers of the South Gondar community had unsafe practice measures in managing people with epileptic seizure episodes. Greater emphasis should be taken on focusing on individuals who could not read and write, in the provision of health education and /or training for the community to help them for acquiring good knowledge and a positive attitude about and towards epilepsy.